Predicting the next decade of tourism gender research. (January 2018) - Pritchard, Annette
Abstract: This article is an opinion piece, which briefly reviews the ways in which tourism is a hugely important sector for women's employment and entrepreneurship opportunities and ultimately for their life, leisure and business experiences. Its main purpose is to speculate on the future of tourism gender research and practice over the next decade. It suggests that, despite a maturing of the field, research utilising qualitative and feminist methods of inquiry continues to struggle for legitimacy in a field dominated by (post)scientific paradigms and approaches. The piece describes the role senior academics must play to shape a vibrant future for gender studies, through mentoring and by holding knowledge structures and hierarchies to account. The piece concludes by highlighting two areas in which tourism gender scholars could lead research on gendered human experiences in the next decade, namely AI and robotics and sexual exploitation and harassment.